2017
DOI: 10.3390/ijgi6050150
|View full text |Cite
|
Sign up to set email alerts
|

Change of Land Use/Cover in Tianjin City Based on the Markov and Cellular Automata Models

Abstract: Abstract:In recent years, urban areas have been expanding rapidly in the world, especially in developing countries. With this rapid urban growth, several environmental and social problems have appeared. Better understanding of land use and land cover (LULC) change will facilitate urban planning and constrain these potential problems. As one of the four municipalities in China, Tianjin has experienced rapid urbanization and such trend is expected to continue. Relying on remote sensing (RS) and geographical info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…A similar pattern of agricultural land loss can be seen in previous studies conducted in P.O. Lwin in Myanmar [5], Hangzhou in China [3], Tianjin in China [72], Baguio in the Philippines [5], Tehran in Iran [44], and Kandy in Sri Lanka [11].…”
Section: Spatiotemporal Lulc Changes and Driving Forcessupporting
confidence: 85%
“…A similar pattern of agricultural land loss can be seen in previous studies conducted in P.O. Lwin in Myanmar [5], Hangzhou in China [3], Tianjin in China [72], Baguio in the Philippines [5], Tehran in Iran [44], and Kandy in Sri Lanka [11].…”
Section: Spatiotemporal Lulc Changes and Driving Forcessupporting
confidence: 85%
“…The Markov chain model, is a stochastic modelling procedure, extensively used for land use land cover change modelling. This model forecasts the future land use land cover from time t = 1 to another time t + 1 [63], on the basis of the transition probability matrix and the transition area matrix of each land use land cover class [47]. The transition matrix represents the probability of land use land cover change in the observed time period from one land use group to another [18,64,65].…”
Section: Markov Change Modelmentioning
confidence: 99%
“…Furthermore, the western development, the Three Gorges project, and the policy of returning farmlands to forests have resulted in changing land use patterns in Chongqing. In addition, the overall planning of the government and the functional orientation of each district and county have also had a profound impact on urban land use change [44][45][46][47].…”
Section: The Impact Of Government Policy On Land Use Changementioning
confidence: 99%
“…Land use changes in the four special municipalities of China, namely Beijing, Tianjin, Shanghai, and Chongqing, have received considerable attention. For example, it has been found that between 1999 and 2017, the built-up area increased and arable and forest land decreased in Beijing [44], where more than 10% of the cropland areas were transformed into built-up areas [45]. This is the main characteristic of land use change in Shanghai, where the expansion of the urban construction land occupied vast areas of farmland and forest land [46].…”
Section: Introductionmentioning
confidence: 99%